2021
DOI: 10.1177/09636897211024942
|View full text |Cite
|
Sign up to set email alerts
|

The Systematic Effect of Mesenchymal Stem Cell Therapy in Critical COVID-19 Patients: A Prospective Double Controlled Trial

Abstract: The aim of this clinical trial was to control the cytokine storm by administering mesenchymal stem cells (MSCs) to critically-ill COVID-19 patients, to evaluate the healing effect, and to systematically investigate how the treatment works. Patients with moderate and critical COVID-19 clinical manifestations were separated as Group 1 (moderate cases, n = 10, treated conventionally), Group 2 (critical cases, n = 10, treated conventionally), and Group 3 (critical cases, n = 10, treated conventionally plus MSCs tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
168
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(179 citation statements)
references
References 35 publications
4
168
1
6
Order By: Relevance
“…According to the World Health Organization (WHO), the cumulative number of deaths due to COVID-19 has surpassed 5.5 million globally. Multiple studies have shown that MSC therapy can significantly reduce the incidence and mortality of critical illness (Table 3 ) [ 14 19 ]. For example, Shu et al [ 14 ] found the mortality in the MSC treatment group was zero.…”
Section: Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…According to the World Health Organization (WHO), the cumulative number of deaths due to COVID-19 has surpassed 5.5 million globally. Multiple studies have shown that MSC therapy can significantly reduce the incidence and mortality of critical illness (Table 3 ) [ 14 19 ]. For example, Shu et al [ 14 ] found the mortality in the MSC treatment group was zero.…”
Section: Efficacymentioning
confidence: 99%
“…Several published clinical trials indicate that MSCs can effectively control the expression of inflammatory cytokines in COVID-19 patients [ 14 16 , 18 , 19 ]. Several studies have reported that proinflammatory cytokines, such as interleukin (IL)-8, tumor necrosis factor (TNF)-α, CRP, IL-6, INF-γ, IL-2, IL-12, and IL-17A, decreased significantly after MSC infusion, while anti-inflammatory cytokines IL-4 and IL-10 increased significantly [ 14 , 15 , 18 ].…”
Section: Efficacymentioning
confidence: 99%
“…Phase I and II clinical studies have shown that MSCs transplantation is a safe and potentially effective method for the treatment of moderate to severe ARDS [63,64]. Besides, recent exploratory clinical studies showed that MSCs treatment was associated with improvements in mortality, dyspnea and chest imaging findings for severe and critically ill COVID-19 patients [65][66][67][68][69]. And phase I and II clinical trials have also shown that intravenous MSCs infusion in patients with moderate and severe COVID-19 is safe and well tolerated [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, MSC infusions had a relatively quick and lasting effect, by decreasing pro-inflammatory cytokines (TNFα) and inflammatory markers (i.e., CRP), and increasing anti-inflammatory cytokines (IL10) and growth factors (KGF). In their CT article, Adas et al 7 reported that a MSC treated patient group had a shorter ICU length of stay and fewer deaths. The Senegaglia et al .…”
Section: Introductionmentioning
confidence: 99%
“…MSC have been beneficial in animal models of ARDS and were used to treat patients suffering from influenza A (H7N9 infections) 9 , 12 , 14 . In critically ill COVID-19 patients who have failed to respond to all other treatments, MSC have been used almost as a last-ditch effort 7 , 11 , 12 . Fortunately, MSC infusions had a relatively quick and lasting effect, by decreasing pro-inflammatory cytokines (TNFα) and inflammatory markers (i.e., CRP), and increasing anti-inflammatory cytokines (IL10) and growth factors (KGF).…”
Section: Introductionmentioning
confidence: 99%